DIPLOMATIC TRANSLATION ERRORS THAT CHANGED HISTORY - Tukhtaeva Zarina (Bright Mind Publishing, 2025)
This article explores the ways that significant mistakes in diplomatic translation have influenced world history. Long-lasting diplomatic rifts, military escalations, and unsuccessful peace negotiations have all resulted from misunderstandings and incorrect translations. This study emphasises the critical function of linguistic accuracy in international diplomacy by looking at historical examples like Khrushchev's famous "We will bury you" speech and the U.S.-Japan communication prior to the Hiroshima bombing.
Keywords: Diplomatic translation, historical miscommunication, international relations, translation errors.